PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) dan LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETUR ON ASSET (ROA) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - ERMAWATI -; DJOKO SETYADI; HERRY RAMADHANI (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
Bank is one of the financial institution which have activities to raise funds from public in the form of savings and distribute them to the public in from of credit or other form. The purpose of the banking business is gain profit. Ability of the banks in gain profit is measured by return on assets (ROA). The purpose of this research is to examine influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), BOPO and Loan to Deposit Ratio (LDR) through Return On Asset (ROA) of banking company listed at Indonesian Stok Exchange during 2011-2014.Research using purposive sampling method for taking samples. Data obtained on the basis of publication Annual Bank, obtained 20 samples of Bank. Samples used in this research are banking company listed at Indonesian Stock Exchange on period 2011-2014. Analysis technique used is multiple linear regression analysis. The results of this research found that Capital Adequacy Ratio (CAR) hasn’t significant negative effect to Return On Asset (ROA), Non Performing Loan (NPL) hasn’t significant positive effect to Return Asset (ROA), BOPO has significant negative effect to Return On Asset (ROA), and Loan to Deposit Ratio (LDR) hasn’t significant positive effect to Return On Asset (ROA).Keywords : CAR , NPL , ROA , ROA and LDR